2020
DOI: 10.1590/0034-7167-2018-0899
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and validation of a booklet on diabetes for Community Health Workers

Abstract: ABSTRACT Objectives: to develop and validate a diabetes booklet for Community Health Workers. Methods: methodological study developed in seven steps: Bibliographic review; Development of the booklet; Calculation of readability and comprehensibility scores; Validation of the booklet by the committee of judges; Discussion between experts; Validation of the booklet by the target audience; and Final discussion between experts. Validation was performed by 10 judges via e-Surv and on a face-to-face test wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
0
8
0
8
Order By: Relevance
“…The results corroborate other investigations that used content validation in the construction of care technologies to promote health in chronic diseases. 26,27 As demonstrated in a previous study, 18 the initial choice of the medical professional to illustrate the belief, both in the video and the messages, occurred because only this member of the health care team was cited as a positive reference for drug treatment. However, following and agreeing with the suggestion of most specialists, who were nurses and contributed massively to the follow-up of this clientele at different levels of health care, this image was modified.…”
Section: Discussionmentioning
confidence: 95%
“…The results corroborate other investigations that used content validation in the construction of care technologies to promote health in chronic diseases. 26,27 As demonstrated in a previous study, 18 the initial choice of the medical professional to illustrate the belief, both in the video and the messages, occurred because only this member of the health care team was cited as a positive reference for drug treatment. However, following and agreeing with the suggestion of most specialists, who were nurses and contributed massively to the follow-up of this clientele at different levels of health care, this image was modified.…”
Section: Discussionmentioning
confidence: 95%
“…This conferred a differential to the material and was essential to the construction process. Similar studies in Brazil have conducted surveys with the target audience about their knowledge on the subject, in the preparation phase of an educational manual (23)(24)(25) .…”
Section: Discussionmentioning
confidence: 99%
“…The comprehension of the texts and coherence of the illustrations also obtained satisfactory CVI scores, indicating that the information used is appropriate. This evaluation methodology is observed in several publications on the construction and validation of educational technologies (18)(19)(20)(23)(24) . The overall CVI of the educational material showed a high level of agreement, corroborating other Brazilian methodological studies on the development of educational technologies that identified similar findings (18)(19)(20)(25)(26)(27) .…”
Section: Discussionmentioning
confidence: 99%
“…A organização do processo de trabalho e a em saúde e auxiliar na CE, tem sido uma tendência na enfermagem como a implantação de protocolo 21 , o desenvolvimento de aplicativo móvel para avaliação/cuidado dos pés de pessoas com DM [16][17] , construção de vídeos educativos para pacientes e cuidadores sobre a aplicação de insulina 23 e elaboração e validação de cartilha sobre diabetes 23 .…”
Section: E14unclassified